Plant phylogenetic diversity of tropical mountaintop rocky grasslands: local and regional constraints - de Mattos, Jacqueline Salvi; Morellato, Leonor Patrícia Cerdeira; Camargo, Maria Gabriela Gutierrez; Batalha, Marco Antonio (Plant ecology, 2019)
Mountains are interesting systems for studying patterns of diversity distribution and the role of environmental filters and competition on community assembly. According to the phylogenetic niche conservatism theory, the co-occurrence of closely related species might indicate that environmental filters are more important than competition when structuring communities in time and space. We investigated the patterns of phylogenetic diversity and the influence of environmental filters in the Brazilian rocky grasslands and tested the influence of phylogenetic niche conservatism. We placed 180 plots of 1 m² in five sites along an altitudinal gradient at the Cipó Mountains (Espinhaço Range, southeastern Brazil) and surveyed all vascular plant species and edaphic variables. We assessed the phylogenetic diversity of the communities by calculating the phylogenetic species variability and phylogenetic species richness. These measures were related to altitude and the edaphic variables through a principal component analysis and regressions. Phylogenetic species variability decreased towards higher altitudes and less fertile sites, whereas phylogenetic species richness increased. Thus, the number of species and the degree of phylogenetic clustering increased with increasing altitude, suggesting that the intensity of abiotic factors acting as environmental filters increased with altitude and could be constraining species in the community to a smaller number of clades.